Aplikasi Kolaborasi Penulisan dan Penyuntingan Berbasis Web untuk Peningkatan Mutu Karya Ilmiah Mahasiswa - Arafah Husna; Sihkabuden; Eka Pramono Adi (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2016)
The student community needs a vehicle to construct knowledge in the form of collaborative scientific writing. Students in the Department of Educational Technology, State University of Malang must have the opportunity to make contributions that will improve the quality of learning and have an impact on society. Managing scientific writing knowledge in a collaborative manner is the main opportunity to achieve significant improvements in student performance in the Department of Educational Technology, State University of Malang. How to develop specific scientific writing collaborative media for students in the Department of Educational Technology, State University of Malang and how to conceptualize Web technology. 2.0 with Wiki and the facilities in it enable students in the Department of Educational Technology, State University of Malang to create, publish and share digital content in new social communities and communities that may already exist. Research objectives are to produce a scientific writing collaboration system model between students in the University of Educational Technology Department environment Negeri Malang is web-based and publishes scientifically regarding the management of student collaboration. The method of developing the Learning model uses the Davidson-Shivers and Rasmussen (2007) model and is selected based on its suitability to the needs of system development characteristics.